Análise crítica da legislação brasileira de segurança e saúde ocupacional: o caso da exposição a agentes químicos - Moreira, José Roberto da Rocha (2010)
The purpose of this paper is to present a critical analysis of Brazilian occupational safety legislation. The study focuses on the issue of chemical agent tolerance levels and covers areas related, for example, to insalubrity and the concepts of occupational hygiene applied to the control of chemical hazards. With the objective of assessing the concepts and current limits of Brazilian legislation, extensive research of existing literature related to the evolution of scientific knowledge on occupational exposure limits was conducted. In order to determine the criteria used to revise and update Brazilian standards, interviews were conducted with professionals directly related to the issuance and review of Brazilian occupational safety legislation. Field work included visits to companies that employ chemical substances in their services and production processes. This phase also served to identify the level of information and procedures adopted by these companies in the control of occupational exposure to chemical agents. Based on the results of the bibliographical and field research, proposals for the prevention of illnesses to workers exposed to chemical substances in the workplace are presented